Toward clinical and molecular dissection of frontonasal dysplasia with facial skin polyps: From Pai syndrome to differential diagnosis through a series of 27 patients. Issue 7 (21st April 2022) - Lehalle, Daphné; Bruel, Ange‐Line; Vitobello, Antonio; Denommé‐Pichon, Anne‐Sophie; Duffourd, Yannis; Assoum, Mirna; Amiel, Jeanne; Baujat, Geneviève; Bessieres, Bettina; Bigoni, Stefania; Burglen, Lydie; Captier, Guillaume; et al.
Abstract: Unique or multiple congenital facial skin polyps are features of several rare syndromes, from the most well‐known Pai syndrome (PS), to the less recognized oculoauriculofrontonasal syndrome (OAFNS), encephalocraniocutaneous lipomatosis (ECCL), or Sakoda complex (SC). We set up a research project aiming to identify the molecular bases of PS. We reviewed 27 individuals presenting with a syndromic frontonasal polyp and initially referred for PS. Based on strict clinical classification criteria, we could confirm only nine (33%) typical and two (7%) atypical PS individuals. The remaining ones were either OAFNS (11/27—41%) or presenting with an overlapping syndrome (5/27—19%). Because of the phenotypic overlap between these entities, OAFNS, ECCL, and SC can be either considered as differential diagnosis of PS or part of the same spectrum. Exome and/or genome sequencing from blood DNA in 12 patients and from affected tissue in one patient failed to identify any replication in candidate genes. Taken together, our data suggest that conventional approaches routinely utilized for the identification of molecular etiologies responsible for Mendelian disorders are inconclusive. Future studies on affected tissues and multiomics studies will thus be required in order to address either the contribution of mosaic or noncoding variation in these diseases.